Hepatocellular Carcinoma Risk Assessment for Patients With Advanced Fibrosis After Eradication of Hepatitis C Virus. Issue 3 (22nd October 2021) - Tamaki, Nobuharu; Kurosaki, Masayuki; Yasui, Yutaka; Mori, Nami; Tsuji, Keiji; Hasebe, Chitomi; Joko, Kouji; Akahane, Takehiro; Furuta, Koichiro; Kobashi, Haruhiko; Kimura, Hiroyuki; Yagisawa, Hitoshi; et al.
Abstract : The identification of patients with advanced fibrosis who do not need any further hepatocellular carcinoma (HCC) surveillance after the eradication of hepatitis C is pivotal. In this study, we developed a simple serum‐based risk model that could identify patients with low‐risk HCC. This was a nationwide multicenter study involving 16 Hospitals in Japan. Patients with advanced fibrosis (1, 325 in a derivation cohort and 508 in a validation cohort) who achieved sustained virological responses at 24 weeks after treatment (SVR24) were enrolled. The HCC risk model at any point after SVR24 and its change were evaluated, and subsequent HCC development was analyzed. Based on the multivariable analysis, patients fulfilling all of the factors (GAF4 criteria: gamma‐glutamyl transferase < 28 IU/L, alpha‐fetoprotein < 4.0 ng/mL, and Fibrosis‐4 Index < 4.28) were classified as low‐risk and others were classified as high‐risk. When patients were stratified at the SVR24, and 1 year, and 2 years after SVR24, subsequent HCC development was significantly lower in low‐risk patients (0.5‐1.1 per 100 person‐years in the derivation cohort and 0.9‐1.1 per 100 person‐years in the validation cohort) than in high‐risk patients at each point. HCC risk from 1 year after SVR24 decreased in patients whose risk improved from high‐risk to low‐risk (HCC incidence: 0.6 per 100 person‐years [hazard ratio (HR) = 0.163 in the derivation cohort] and 1.3 per 100 person‐years [HR = 0.239 in the validation cohort]) than in those with sustained high risk. Conclusion: The HCC risk model based on simple serum markers at any point after SVR and its change can identify patients with advanced fibrosis who are at low HCC risk, and these patients may be able to reduce HCC surveillance. Abstract : image